2015
DOI: 10.1007/s11095-015-1771-6
|View full text |Cite
|
Sign up to set email alerts
|

Novel Gefitinib Formulation with Improved Oral Bioavailability in Treatment of A431 Skin Carcinoma

Abstract: Purpose Oral administration of anticancer agents presents a series of advantages for patients. However, most of the anti-cancer drugs have poor water solubility leading to low bioavailability. Methods Controlled released spray dried matrix system of Gefitinib with hydroxypropyl β-cyclodextrin, chitosan, hydroxy propyl methyl cellulose, vitamin E TPGS, succinic acid were used for the design of formulations to improve the oral absorption of Gefitinib. Spray drying with a customized spray gun which allows simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 68 publications
(66 reference statements)
1
26
0
Order By: Relevance
“…Significant reduction in the VEGF levels was observed in tumor lysates in C-DIM treated groups. The role of VEGF in angiogenesis is very well documented in several studies and antiangiogenic effects of C-DIM were also reported in previous studies, which are in agreement with our present findings [2,7]. Our NLC based oral formulation approach may provide superior anticancer drug delivery strategies for poorly water soluble drugs to improve the pharmacokinetics problems associated with several interesting anticancer agents.…”
Section: Discussionsupporting
confidence: 93%
“…Significant reduction in the VEGF levels was observed in tumor lysates in C-DIM treated groups. The role of VEGF in angiogenesis is very well documented in several studies and antiangiogenic effects of C-DIM were also reported in previous studies, which are in agreement with our present findings [2,7]. Our NLC based oral formulation approach may provide superior anticancer drug delivery strategies for poorly water soluble drugs to improve the pharmacokinetics problems associated with several interesting anticancer agents.…”
Section: Discussionsupporting
confidence: 93%
“…The colonies/spheroids grown in each well were fixed in glutaraldehyde and stained with crystal violet. Number of colonies was counted with an optical microscope and colony sizes were measured and representative spheroid images were captured [25]. …”
Section: Methodsmentioning
confidence: 99%
“…ASDs have been reported to enhance the pharmacokinetics of several anticancer drugs [24][25][26]. Also, ASDs have been reported to improve the therapeutic outcomes of anti-cancer drugs such as vemurafenib and gefitinib [26][27][28]. Hence, ASDs represent a promising formulation to enhance the dissolution of abiraterone and improve its pharmacokinetic properties, once a suitable manufacturing technique is found.…”
Section: Introductionmentioning
confidence: 99%